DEVELOPMENT OF HERBIFY APPLICATION WITH AI INTEGRATED UTILIZING YOLO V8 FOR OPTIMIZING HERBAL POTENTIAL IN INDONESIA - Ahmad Fajruddin Syauqi; Prasetya, Didik Dwi (Jurnal Teknik Informatika (Jutif), 2024)
Indonesia is known as the home to 80% of the world's medicinal plant species, with an estimated 25,000-30,000 potential plants. However, this is in stark contrast to the current situation of limited access to herbal information, leading to restricted consumption and distribution of herbal products. The numerous digital platforms providing herbal data still fail to address this issue, as the information provided does not cater to the users' needs. Therefore, to address the current challenges in the Indonesian herbal industry, researchers developed an AI-integrated application called Herbify. The application was developed using the Agile Software Development Life Cycle method, chosen to meet user needs with a user-centered design approach. From this research, a mobile application with two main features, namely 'Herbalpedia' and 'Scanherbal,' was developed. Measurements through three methods: mAP matrix, usability tests, and user experience questionnaires (UEQ), yielded positive results. The measurement results show that the trained model achieved a 94.6% mAP with an inference time of 0.07965 seconds. Furthermore, the usability test results of the application show a 0% mission unfinished rate, with an average completion time of 10 seconds. The UEQ results indicate that the application has high usability, trustworthiness, and information quality. Based on these results, it can be concluded that Herbify has great potential to effectively optimize herbal potentials in Indonesia.